Choosing an Appropriate Wavelet for VARX Time Series Model Analysis - Elias, intisar; Hussein Ali, Taha (Journal of Economics and Administrative Sciences, 2025)
The paper purports to improve the accuracy of VARX (vector autoregressive with exogenous variables) models adopted for economic time series analysis through wavelet transform techniques applied for noise reduction. The research assessed various wavelet types, including Coiflets, Daubechies, Symlets, Biorthogonal, and Reverse Biorthogonal, for the most appropriate wavelet to be used for improving the performance of the models. Furthermore, it made use of the Akaike Information Criterion (AIC) and Bayesian Information Criterion (BIC) for evaluating the efficacy of each wavelet in the dimension of noise reduction and predictive accuracy enhancement.It is conclusively deduced that preprocessing through wavelet-based techniques markedly improves the reliability of VARX models, as it removes short-term noise without affecting the long-term trends in the economy. Application of Daubechies and Reverse Biorthogonal wavelets has emerged better in all size categories in reducing AIC and BIC values. Thus, the study lauds wavelet denoising techniques in associating industries with finance to provide sound arguments for policymakers and economists to analyze more accurately complex economic relations.This work advances development in econometric modeling, detailing the importance of wavelet transformations in improving economic forecasts. Future studies should explore combining machine learning techniques with wavelet-based VARX models for further improvements in forecasting capabilities.